In-vitro evaluation of the anti-cariogenic effect of a hybrid coating associated with encapsulated sodium fluoride and stannous chloride in nanoclays on enamel - Sávio José Cardoso BEZERRA; Ítallo Emídio Lira VIANA; Idalina Vieira AOKI; Simone DUARTE; Anderson Takeo HARA; Taís SCARAMUCCI (University of São Paulo, 2022)
Abstract Objective The aim of this study is to test, in vitro, the anti-cariogenic effect of experimental hybrid coatings, with nano clays of halloysite or bentonite, loaded with sodium fluoride or with a combination of sodium fluoride and stannous chloride, respectively. Methodology The varnish Fluor Protector (1,000 ppm of F-) was used as positive control and no treatment was the negative control. Enamel specimens (5 mm × 5 mm) were obtained from bovine teeth. The specimens (n=10) had their surfaces divided into two halves (5 mm × 2.5 mm each), in which one half received one of the treatments (Hybrid; Hybrid + NaF; Hybrid + NaF + SnCl2; Hybrid + NaF Loaded; Hybrid + NaF + SnCl2 Loaded). The specimens were submitted to a cariogenic challenge using a biofilm model (S. mutans UA159, for 5 days). Enamel surfaces both under and adjacent to the treated area were analyzed for mineral loss and lesion depth, by transverse microradiography. The pH of the medium was measured twice a day, and the fluoride release was analyzed. Additional specimens were submitted to confocal analysis. Results Data were statistically analyzed by two-way ANOVA followed by Tukey test (α=0.05). None of hybrid groups were able to reduce the lesion depth; the Hybrid + NaF group, however, was able to reduce mineral loss differing from the negative control (p=0.008). The groups showed no significant difference in the pH measurement and fluoride release. Confocal analysis confirmed that for all groups the biofilm growth was similar. Conclusion None of the hybrid groups reduced lesion depth, but the Hybrid + NaF group was able to promote protection against mineral loss.